Shewhart-type location control chart based on capability indices Cp and Cpk applied to profile monitoring - Morales, Daily (2021)
Through their statistical limits, statistical control charts are essential tools for process monitoring and control, helping to interpret its stability and detect deviations when the process is under the action of special causes. This sensitivity is an advantage for processes needing precise control but is a drawback where some slack in the process is permissible. Even though small attributable causes may be inherent to the process, their removal may become impossible, impractical, or expensive, and control charts need to be "desensitized" in detecting small shifts that are not necessarily of practical significance. The increasing availability of data made possible by the intensive use of sensors and data collectors, typical of Industry 4.0, have made of profile monitoring an up-and-coming area of research,and the location control chart a standing out alternative due to its applicability and simplicity, keeping all the data information observed in each location where the profile needs to be evaluated. This thesis discusses the need for desensitization of the location control charts to ensure that signs of an out-of-control process that do not present a high risk of producing non-conforming items are ignored. Using process capability indices Cp and Cpk, this thesis aimed to propose and evaluate a location control graph model with expanded limits based on Shewhart-type control charts, considering its practical and economic significance. By comparing the results obtained for the location control chart using the traditional approach and the location control chart with expanded limits based on Cp and Cpk proposed in this thesis, was observed that the expanded control limits had performed better. There was a significant reduction in the likelihood of signaling that the process is out-of-control when this is irrelevant or, at least, does not present practical or economic significance. Since the location control chart developed does not aim to control the stability of the process but to prevent the process from producing items outside the specification limits, the results demonstrate that, from the economic point of view, it constitutes a more interesting alternative to the traditional approach.